Cultural validation of the multidimensional peer victimization scale in Nigerian children (2007)
This study attempted cultural validation of the Multidimensional Peer Victimization Scale for use with Nigerian children. In it, 240 primary school pupils in Grades 4and 5 (13 I boy, and 109 girl,; age 7 to 12) purposively selected from five nursery/primary schools in Ibadan, Nigeria, participated. The Multidimensional Peer Victimization Scale was administered, and analysis yielded Cronbach's alpha os.7X8 for internal consistency and split-half reliability of .76. Principal component analysis identified four factors with Eigenvalues greater than 1.00, with all items loading above .49. Gender and age effects were not significant on total peer victimization score, although significant gender and age differences were observed on some subscales. The scale correlated significantly with the Bus, and Durkee Aggression Scale. Results suggest the Multidimensional Peer Victimization Scale can be used to measure Nigerian children's experience of peer victimization and provide an initial step toward further cross-cultural work on peer victimization.